Private, Social and Self-Insurance for Long-Term Care in the Presence of Family Help - A Political Economy Analysis - Philippe De Donder; Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study the political determination of the level of social long-term care insurance when voters also choose private insurance and saving amounts. Agents differ in income, probability of becoming dependent and of receiving family help. Social insurance redistributes across income and risk levels, while private insurance is actuarially fair. The income-to-risk ratio of agents determines whether they prefer social or private insurance. Family support crowds out the demand for both social and, especially, private insurance, as strong prospects of family help drive the demand for private insurance to zero. The availability of private insurance decreases the demand for social insurance but need not decrease its majority chosen level.
Keywords: D72; I13; J14; 330; long-term care; social insurance; familism; crowding out; weak and strong prospects of family help; voting